2000
DOI: 10.1291/hypres.23.39
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Dependent Calcium Release from Vascular Smooth Muscle Mitochondria.

Abstract: Interest in mitochondrial calcium (Ca2+) uptake and release waned as it became apparent that sarcoplasmic reticulum calcium stores dominate the control of cytoplasmic calcium concentration.Our recent demonstration of a very large rise in vascular smooth muscle (VSM) cytoplasmic sodium (Na+) concentration after inhibition of the sodium, potassium-ATPase (sodium pump) led us to several questions. Do VSM mitochondria show Na+-dependent Ca2+ release? Are the documented changes in cytoplasmic Na+ concentration suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Thapsigargin (1 µM) was added to inhibit ER Ca 2+ uptake. The Ca 2+ indicator arsenazo III (100 µM) was added, and kinetic measurements of absorbance were performed at 650 nm (reference at 685 nm) (76)(77)(78). After one minute, 40 µM CaCl2 was added at every 2 minutes until no further Ca 2+ uptake was observed.…”
Section: Mitochondrial Calcium Retention Capacity (Crc) Analysismentioning
confidence: 99%
“…Thapsigargin (1 µM) was added to inhibit ER Ca 2+ uptake. The Ca 2+ indicator arsenazo III (100 µM) was added, and kinetic measurements of absorbance were performed at 650 nm (reference at 685 nm) (76)(77)(78). After one minute, 40 µM CaCl2 was added at every 2 minutes until no further Ca 2+ uptake was observed.…”
Section: Mitochondrial Calcium Retention Capacity (Crc) Analysismentioning
confidence: 99%
“…Despite the appreciation of NCLX as a mediator of Ca 2+ extrusion from mitochondria, several studies showed that NCLX is also localized on the plasma membrane, endoplasmic reticulum (ER), and possibly other organelles ( Haworth and Hunter, 1979 ; Bernardi, 1999 ; Cai and Lytton, 2004a ; Palty et al, 2004 ; Palty et al, 2006 ; Han et al, 2015 ; Rysted et al, 2021 ). There is also inconsistency between the ability of NCLX to exchange Ca 2+ for Li + nearly as effectively as for Na + ( Palty et al, 2004 ; Roy et al, 2017 ) and the observations that Li + -driven mitochondrial Ca 2+ efflux is only 10–25% of that driven by Na + ( Crompton et al, 1977 ; Tokunaga et al, 2000 ; Rysted et al, 2021 ). In addition, recent studies showed that NCLX knockdown or knockout had little effect on mitochondrial Ca 2+ extrusion in airways smooth muscle and B lymphocytes, respectively ( Emrich et al, 2022 ; Johnson et al, 2022 ).…”
Section: Mitochondrial Ca 2+ Uptake and Release Me...mentioning
confidence: 99%